Clinical observations on the treatment of infantile hemangiomas with topical imiquimod 5% cream - Guo, Zhengtuan; Li, Guowei; Xu, Quan; Gao, Ya; Li, Peng; Zhang, Xiansheng; Duan, Yitao; Guo, Xinkui; Zheng, Baijun (Journal of Nanjing Medical University, 2009)
Objective： To observe the efficacy and safety of topical imiquimod 5% cream in the treatment of uncomplicated infantile hemangiomas （IHs）. Methods： A total of 68 IHs were treated with topical imiquimod 5% cream. Among them, 36 were superficial, 22 were mixed, and 10 were deep. The size of IHs ranged from 1.0 cm × 1.5 cm to an area of a whole forearm. All the hemangiomas were in a proliferative stage. Imiquimod was applied 3 times weekly in 44 patients and 5 times weekly in 24 patients for up to 36 weeks. Results： All superficial IHs improved, and 18 achieved complete clinical resolution, 10 had excellent improvement, 5 showed moderate improvements, and 3 patients displayed minimal improvement. Two mixed IHs showed excellent improvement, 3 showed moderate improvement and 5 manifested minimal improvements. The remaining 12 mixed IHs and all deep IHs did not respond to the therapy. The total incidence of local adverse events was 58.82%（40/68）, which included erythema or edema, local itching, incrustation or peeling, erosion or ulceration, although most of these were mild to moderate reactions and did not affect the treatment. Scarring occurred in 2 mixed IHs. No systemic side effects developed. Conclusion： Imiquimod 5% cream may be a safe and effective alternative for the treatment of superficial IHs and some mixed IHs in which the superficial component predominates. An appropriate treatment duration for proliferative IHs treated with this therapy may be 24 weeks. Some local adverse events, such as crusting and erosion with possible scarfing potential may occur and should be addressed by prompt, but temporary, discontinuation of the imiquimod. Topical imiquimod 5% cream can be prudently used in the treatment of IHs larger than 5.0 cm × 5.0 cm in newborns and infants less than 6 months of age. To our knowledge, this is the largest IH group treated with imiquimod that has been reported in the literature to date.